OPTIMALISASI PENGENDALIAN PERSEDIAAN BAHAN BAKU MELALUI METODE ECONOMIC ORDER QUANTITY DAN JUST IN TIME - Indra Maula Sari; Amalia Ma’rifatul M (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Effective inventory control is essential for the success of a company's operations. PT XYZ, a leading manufacturer of spices and flavorings in Indonesia, faces ongoing challenges in maintaining high product quality and consistent market availability. Inefficient inventory management can result in both shortages and excess stock, disrupting customer order fulfillment and increasing storage costs. This study analyzes and compares the effectiveness of the Economic Order Quantity (EOQ) and Just In Time (JIT) methods in optimizing supply chain efficiency at PT XYZ. The analysis uses data on frozen chicken meat requirements for the 2024 production period, totaling 17.325.593 kg across 214 orders. The research includes determining ordering strategies, calculating optimal quantities using the EOQ method, and developing JIT-based order patterns. Key parameters evaluated include order quantity, frequency, delivery pattern, and total inventory cost. The results indicate that the JIT method is the most cost-efficient, with total expenses of Rp 4.086.573,74, followed by the EOQ method at Rp 9.583.864,95, while the company’s current policy incurs Rp 42.546.728,97. Compared to the existing system, the JIT method reduces total inventory costs by approximately 90,39%, and the EOQ method by 77,47%. The study concludes that JIT offers the most effective cost reduction, although its successful implementation requires a highly reliable supply chain to ensure timely delivery and continuous production.